Testing the effects of a TRIZ invention instruction program on creativity beliefs, creativity, and invention teaching self-efficacy - Park, Su Jin (Education and information technologies, 2023)
The purpose of this study was to develop an invention instruction program based on the Theory of Inventive Problem Solving (TRIZ) for preservice invention teachers and test the effects of the program on teachers’ creativity beliefs, creativity, and invention teaching self-efficacy. The subjects of this study were preservice teachers who were enrolled in a four-week (eight sessions) TRIZ invention course at a university in South Korea. A quasi-experimental method was used to incorporate TRIZ instructional strategies into an invention course that taught invention principles and hands-on activities. Results showed that the TRIZ instructional method significantly increased creativity beliefs, creativity, and invention teaching self-efficacy in preservice teachers. Interestingly, the TRIZ program had different effects on subdimensions of creativity. Results of the study suggest that TRIZ is an effective instructional method that can be used to increase teachers’ creativity, change their beliefs about creativity, and boost confidence in their invention teaching ability. Limitations and suggestions for future study are also discussed.